Linagliptin in Combination With Metformin Ameliorates Diabetic Osteoporosis Through Modulating BMP-2 and Sclerostin in the High-Fat Diet Fed C57BL/6 Mice - Nirwan, Nikita; Vohora, Divya (Frontiers in Endocrinology, 2022)
Background: Diabetic osteoporosis is a poorly managed serious skeletal complication, characterized by high fracture risk, increased bone resorption, reduced bone formation, and disrupted bone architecture. There is a need to investigate drugs that can improve bone health along with managing glycemic control. DPP-4 inhibitors and metformin have proven benefits in improving bone health. Here, we investigated the effects of linagliptin, a DPP inhibitor, and metformin alone and in combination to treat diabetic osteoporosis in high-fat-fed mice. Methods: C57BL/6 mice were kept on the high-fat diet (HFD) for 22 weeks to induce diabetic osteoporosis. Linagliptin (10mg/Kg), metformin (150mg/Kg), and their combination were orally administered to the diabetic mice from the 18th-22nd week. Femur and tibial bone microarchitecture together with bone mineral density (BMD) were evaluated using µCT and histopathological changes were assessed. Further, bone turnover biomarkers namely bone morphogenetic protein-2 (BMP-2), sclerostin, tartrate-resistant acid phosphatase (TRAP), osteocalcin, alkaline phosphatase (ALP), calcium, and pro-inflammatory cytokines were assessed. Additionally, metabolic parameters including body weight, fasting blood glucose (FBG), glucose & insulin tolerance, lipids profile, and leptin were measured. Results: HFD feeding resulted in impaired bone microarchitecture, reduced BMD, distorted bone histology, and altered bone turnover biomarkers as indicated by the significant reduction in bone ALP, BMP-2, osteocalcin, and an increase in sclerostin, TRAP, and serum calcium. Interestingly, treatment with linagliptin and its combination with metformin significantly reverted the impaired bone architecture, BMD, and positively modulated bone turnover biomarkers, while metformin alone did not exhibit any significant improvement. Further, HFD induced diabetes and metabolic abnormalities (including an increase in body weight, FBG, impaired glucose and insulin tolerance, leptin, triglycerides, cholesterol), and pro-inflammatory cytokines (TNF-alpha and IL-1β) were successfully reversed by treatment with linagliptin, metformin, and their combination. Conclusion: Linagliptin and its combination with metformin successfully ameliorated diabetic osteoporosis in HFD-fed mice possibly through modulation of BMP-2 and sclerostin. The study provides the first evidence for the possible use of linagliptin and metformin combination for managing diabetic osteoporosis.